The current status of natural and artificial radiation in İstanbul 36 years after chernobyl, preceding a potential nuclear threat - Guenay, Osman; Ozden, Selin; Pehlivanoglu, Serpil Akozcan (SPRINGER, 2024)
In this study, the current status of natural and artificial radioactivity levels in soil samples from the B & uuml;y & uuml;k & ccedil;ekmece and Silivri districts of Istanbul, as well as the Marmara Ere & gbreve;lisi district in Tekirda & gbreve;, has been determined in anticipation of a potential nuclear leakage (e.g. the Zaporizhzhia Nuclear Power Plant). Twenty soil samples were collected from the study area, and the radioactivity concentrations of Ra-226, Th-232, K-40 and Cs-137 were measured using an HPGe detector. The average concentrations of Ra-226, Th-232, K-40 and Cs-137 were found to be 26 +/- 2, 30 +/- 2, 540 +/- 29, 0.55 +/- 0.07 Bq kg(-1), respectively.
Keywords: Natural radiation; Gamma-ray spectrometry; Cs-137 pollution; Annual effective dose; Soil pollution in & Idot; stanbul; RADIOLOGICAL HAZARD INDEXES; SOIL SAMPLES; RADIOACTIVITY LEVELS; DOSE-RATES; SPATIAL-DISTRIBUTION; SEDIMENT SAMPLES; RADIONUCLIDES; CS-137; TH-232; RA-226; Chemistry; Nuclear Science & Technology